Calvin on slavery: Providence and social ethics in the 16th century - Kayayan, Eric (Koers, 2013)
In this article, Calvin’s views on slavery are evaluated within the broader historical context of the practice of slavery during the late Middle Ages and the 16th century, and also in the light of various views inherited from Greek and Roman antiquity. Calvin’s sermons on Deuteronomy, his commentary on Ephesians and 1 Timothy are particularly relevant to this study, as is his earlier commentary on Seneca’s De Clementia. Whilst it appears that the 16th century’s context does not play a central role in Calvin’s assessment of slavery, his exegesis of biblical texts leads him to articulate a strong position with regard to this anthropological and ethical issue, combining the notions of imago Dei [image of God], humanitas [humaneness], providentia Dei [providence of God] and analogical right.